Analisis Pelaksanaan Kurikulum Merdeka pada Mata Pelajaran PJOK Tingkat SMA di Kabupaten Aceh Selatan - Afrizal, Afrizal; Pane, Adelia Putri; Fikri, Azizil (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine the planning, implementation, and evaluation of PJOK learning in the Merdeka Curriculum in three sub-district public high schools, namely Trumon sub-district, Central Trumon sub-district and East Trumon sub-district (Trumon Raya), South Aceh Regency. This type of research is qualitative research. The subjects of this research were 11 PJOK teachers at State High Schools in Trumon Raya, Aceh Regency. The instruments used in this research are observation, interviews, and documentation. For the validity of the data, researchers used the triangulation method. The following research results were obtained: PJOK learning planning in the Independent Curriculum is included in the adequate category. This is proven by the fact that many PJOK teachers are not prepared enough to prepare learning tools for the Independent Curriculum. The implementation of PJOK learning in the Merdeka Curriculum is categorized as adequate because the teacher's learning implementation has been carried out in preliminary, core, and closing stages, and learning is no longer centered on the teacher but on students. Evaluation of PJOK learning in the independent curriculum is categorized as sufficient because the teacher assesses the results of daily tests, mid-semester tests, and end-of-semester tests and assesses them cognitively, psychometrically, and effectively. Conclusion: In planning for PJOK learning in the independent curriculum, it can be concluded that the teacher implementing PJOK learning with the independent curriculum at Se Trumon Raya State High School, South Aceh Regency, is preparing teaching tools quite well. Keywords: Implementation, Independent Curriculum, PJOK